2020
DOI: 10.1111/jfpp.15062
|View full text |Cite
|
Sign up to set email alerts
|

Significance of storage study on ACE inhibitory, antioxidative, antimicrobial activities, and biotransformation of isoflavones of functional fermented soy‐based beverage

Abstract: Soy‐based fermented beverages prepared with potential Lactobacilli provide nutrition with various health beneficial attributes like ACE inhibitory, antioxidative, anti‐microbial activities to the human host. Further, the biotransformation of isoflavones through soy lacto‐fermentation also produces extra benefits to the hosts by preventing hormonal disorders in the post‐menopausal women. In the present study, storage stability and biofunctional properties of the fermented soy‐based beverages (A1 prepared with L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In maize, 2,4-dihydroxy-7-methoxy-2H-1,4-benzoxazin-3(4H)-one (DIMBOA) can resist fungus (Frey et al, 1997). The isoflavones also have antimicrobial functions (Undhad et al, 2021). Research has shown that under the stimulation of pathogenic bacterial infection, tea leaves can increase polyphenols as antibacterial factors, and the cortex of roots and stems can also produce antitoxin (Turkmen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In maize, 2,4-dihydroxy-7-methoxy-2H-1,4-benzoxazin-3(4H)-one (DIMBOA) can resist fungus (Frey et al, 1997). The isoflavones also have antimicrobial functions (Undhad et al, 2021). Research has shown that under the stimulation of pathogenic bacterial infection, tea leaves can increase polyphenols as antibacterial factors, and the cortex of roots and stems can also produce antitoxin (Turkmen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of genistein in the product obtained in such a manner was 2.65 mg/100 mL and, of course, was significantly higher than in the unfermented substrate. It was proven that a fermented soy drink completed with skim milk powder and whey protein concentrate could definitely be a nutritious beverage for people of all ages [ 46 ].…”
Section: Fermentation As a Way To Increase Genistein Contentmentioning
confidence: 99%
“…40 Natural isoflavones in soy conjugate with sugars, which limits their absorption, but they can be hydroxylated into bioavailable form (aglycone) and easily digested via fermentation. 24,43 Serum and total cholesterol were reduced in obese mice fed with a high-fat diet containing 3 0 -hydroxydaidzein (daidzein derivative), a metabolite from fermented soy products. 44 Fermenting chickpea, lentil, and rice flour with LAB (Lactoplantibacillus plantarum and Levilactobacillus brevis) for 16 h generated a gluten-free yogurt-style-snack with enhanced AA profile, antioxidant properties and reduced ANFs (phytic acid, tannins, ⊍-galactosides) content.…”
Section: Introductionmentioning
confidence: 99%
“…The large amounts of peptides and free amino acids (AAs) generated in European dry‐fermented sausages participated in the development of characteristic flavor, with some peptides also exerting antioxidant and ACE inhibitory activities 40 . Natural isoflavones in soy conjugate with sugars, which limits their absorption, but they can be hydroxylated into bioavailable form (aglycone) and easily digested via fermentation 24,43 . Serum and total cholesterol were reduced in obese mice fed with a high‐fat diet containing 3′‐hydroxydaidzein (daidzein derivative), a metabolite from fermented soy products 44 .…”
Section: Introductionmentioning
confidence: 99%